Inovasi Desa Berbasis Kearifan Lokal: Tinjauan Literatur terhadap Praktik Terbaik di Indonesia - Kapisa, Redi Yana; Maulana, Ayi; Sukirman, Ria Fidriyanti (Journal of Digital Community Services, 2025)
Village innovation based on local wisdom is a strategic approach to strengthening sustainable rural development. This study aims to identify best practices from various regions in Indonesia that have successfully implemented innovations by leveraging cultural values, traditional knowledge, and active community participation. The research adopts a literature review method based on scientific publications from the past ten years. The findings show that the success of village innovation is largely influenced by community engagement, inclusive leadership, and multi-sector collaboration. The documented innovations include the development of local flagship products, public services through village-owned enterprises (BUMDesa), and the revitalization of traditional food. These findings are synthesized into a conceptual model that illustrates the innovation cycle, starting from local wisdom as the idea source to the resulting social and economic impacts. This model is expected to serve as a framework for community service programs and can be replicated according to each village’s context. The study also highlights key challenges such as limited human resources and digital infrastructure. Therefore, systematic documentation and village capacity-building are strategic steps to promote broader and more sustainable innovation replication.